Good Governance through Digitalization of Government in Sidomulyo Village, Bangsal District, Mojokerto Regency - Tri Ratna Rinayuhani Rinayuhani; Hajar Nurma Wachidah; Ratnaningrum Z.D (LPPM Institut Pendidikan Nusantara Global, 2025)
Indonesia’s push toward an Electronic-Based Government System (SPBE) seeks to advance good, clean, and high-quality governance across all administrative tiers, including villages. Anchored in Law No. 6/2014 on Villages and the Village Fund Allocation (ADD) framework, many villages are experimenting with digital platforms to strengthen transparency, accountability, participation, and service delivery. This qualitative descriptive study examines the early-stage digitalization of government in Sidomulyo Village, Bangsal District, Mojokerto Regency. Data were collected through document review, field observation, and interviews using key informants directly responsible for digital implementation, including the village secretary and head of government affairs. Findings show that the village website prototype has begun to operationalize core sound governance principles: (1) transparent disclosure of finances, policy documents, and institutional data; (2) NIK-authenticated service access that supports rule-of-law–based inclusivity; (3) streamlined administrative turnaround (1×24 hours) that improves efficiency and responsiveness; and (4) open two-way communication channels that encourage public participation and oversight. Constraints remain limited infrastructure, funding, digital literacy, and the short (three-month) observation window. However, the results indicate promising gains in bureaucratic performance and citizen–government interaction that align with national SPBE targets. Further longitudinal evaluation and technical scaling are recommended.